2020
DOI: 10.1101/2020.04.28.065813
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of MIND Diet Intervention on Cognitive Performance and Brain Structure in Healthy Obese Women: A Randomized Controlled Trial

Abstract: Background and Aim: Previous studies suggested adherence to recently developedMediterranean-DASH Intervention for Neurodegenerative Delay (MIND) associated with cognitive performance. There was no prior Randomized controlled Trial (RCT) to investigate this association. This study aimed to examine the effect of MIND dietary pattern on features of cognitive performance and also changes in brain structure in healthy obese women. Methods:As a total of 50 eligible obese (mean BMI 32 ± 4.31) female adults (mean age … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A systematic review of 13 studies also showed that adherence to the MIND diet was associated with improved cognitive function, especially in older adults (12), while several other studies have reported it to be associated with improved verbal memory and global cognitive performance, as well as a slower rate of cognitive decline after stroke and a lower risk of dementia (6,7,13,14). A recent cross-sectional study and randomised controlled trial (RCT) found that the MIND diet is inversely associated with the odds of reduced HDL-cholesterol and general obesity (15, 16). The MIND diet emphasises the consumption of fatty sh, and long-chain n-3 fatty acids found in sh may reduce amyloid-beta (Aβ) formation and oxidative damage.…”
mentioning
confidence: 99%
“…A systematic review of 13 studies also showed that adherence to the MIND diet was associated with improved cognitive function, especially in older adults (12), while several other studies have reported it to be associated with improved verbal memory and global cognitive performance, as well as a slower rate of cognitive decline after stroke and a lower risk of dementia (6,7,13,14). A recent cross-sectional study and randomised controlled trial (RCT) found that the MIND diet is inversely associated with the odds of reduced HDL-cholesterol and general obesity (15, 16). The MIND diet emphasises the consumption of fatty sh, and long-chain n-3 fatty acids found in sh may reduce amyloid-beta (Aβ) formation and oxidative damage.…”
mentioning
confidence: 99%